Write solutions in simplest radical form.

2x^2-2x-1=0

Answer:

here we can write the subsequent steps:

2(x^2 - x -1/2)=0

x^2 - x -1/2 =0

x^2 - x +1/4 - 1/4 -1/2 =0

(x-1/2)^2 = 3/4

so we get:

x -1/2 = sqrt(3)/2, and

x -1/2 = -sqrt(3)/2

so your solutions are:

x = 1/2 + sqrt(3)/2, and, x= 1/2 - sqrt(3)/2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up